Kadar Karbon Monooksida di Udara pada Badan Jalan Kota Ambon - Tina Amnah Ningsih (Poltekkes Kemenkes Maluku, 2019)
Some types of air pollutants from motor vehicle exhaust gases are carbon monoxide (CO), nitrogen oxides (NOx), sulfur oxides (SOx), hydrocarbons (HC), and others. The increase in the number of motorized vehicles will have a direct impact on the increasing concentration of CO exhaust emissions in the air. This study aims to determine the level of CO gas in the air on the road in Ambon City. The type of research used is descriptive. The sampling location was on the road of Jenderal Sudirman which is one of the main roads in Ambon City which often experiences congestion due to the dense flow of motorized vehicles, especially during the daytime. Measuring CO was done at one point with measurements twice with the duration of sampling for one hour. The results of the examination of CO levels in the air showed that CO levels were low in the morning at 5750 µg / Nm3. While CO levels during the day increased to 8900 µg / Nm3. Based on the results of measurements of CO levels on Jalan Jenderal Sudirman, Sirimau District, Ambon City, it was stated that they met the requirements based on Government Regulation No. 41 of 1999 CO levels in the air with a duration of measurement for 1 hour, amounting <30,000 µg / Nm3. From the results of the research conducted suggested that one of them is the Department of Hygiene and Parks can carry out reforestation in the area of ​​the road body to maintain CO levels that do not pass through the predetermined of Maximum Allowable Concentration (MAC). Keywords: CO levels, air quality, air quality in Ambon City